Enhancing Students' Reading Comprehension through CIRC Method at Vocational High School 2 PGRI Kediri - Ingga, Hero; Khoiriyah; Sulistyani (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This study investigates the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) method in improving students' reading comprehension at SMK PGRI 2 Kediri. The motivation arose from students' difficulties in understanding English narrative texts, often caused by limited vocabulary, low motivation, and ineffective reading strategies. A quantitative approach was used with a one-group pre-test and post-test design, involving 25 students from Class XI Accounting 2. Data was collected through multiple-choice reading comprehension tests administered before and after implementing the CIRC method. The results show a significant improvement, with average scores rising from 48.64 in the pre-test to 80.24 in the post-test. The paired sample t-test revealed a significant difference (p < 0.05), indicating that the CIRC method has a positive impact on reading comprehension. Moreover, CIRC encourages collaborative learning and increases student engagement, fostering a more interactive and enjoyable classroom environment. These social and emotional benefits suggest that CIRC not only enhances academic achievement but also improves classroom dynamics. In conclusion, the CIRC method is an effective strategy for boosting reading comprehension among vocational high school students and is recommended for English teachers seeking innovative, student-centered teaching approaches. Future research could explore the application of this method to other language skills or educational contexts.